A research study on consumer intention to purchase counterfeit international branded products in Melaka City / Hamidah Mohd. Isa and Siti Nur Fathiyah Sa’ad - Mohd. Isa, Hamidah; Sa’ad, Siti Nur Fathiyah (Faculty of Business and Management, 2014)
This research study addresses the issue of consumer intention on buying counterfeit international branded products in Melaka City. This study intends to examine the relationship of social influence, personality or belief and price on consumer purchase intentions in the context of counterfeit international branded products in Melaka. A sample of 80 respondents at the age of 18 years old and above in Melaka City with the help of questionnaires survey containing statements related beliefs about counterfeited branded products was taken. The data were analyzed using Statistical Package for Social Sciences (SPSS). The findings support the independent variables that contributed to the consumer intentions to purchase counterfeit international branded products. There are significant relationships between dependent variable and independent variables in this research study. The results indicated that social influence is the main factor contributing to the intention to purchase counterfeit products. This suggests that the consumers are simply willing to purchase counterfeit products after being influence by the social factors. However, further studies with bigger sample sizes and broader geographical scopes are needed to clarify these findings.